Strategies for the teaching of volleyball through psychomotricity exercises in the boys and girls of educational institutions (Revista Electrónica REDINE, 2020)
The present investigation was framed in the quantitative approach under the principles of the positivist paradigm. The study was based on descriptive fieldwork. Its purpose was to explore strategies to improve the teaching of volleyball through psychomotricity exercises in boys and girls of the Public Educational Institutions of the Tamaca Parish, Iribarren Municipality of Lara State. The sample was made up of fifteen (15) teachers of the Physical Education specialty who work in the Public Institutions in charge of teaching the foundations of the discipline of volleyball. The instrument used was a questionnaire with twelve (12) items in order to define the strategies that specialists use, updates in the area, resources available and the environment in which learning is generated. Among the conclusions that were generated in the study, it can be mentioned that the surveyed teachers deserve training in the theories related to the strategies to develop the technical foundations of volleyball and the motor skills of children who begin in this collective sport. Therefore, it was recommended to implement update workshops on the technical and tactical preparation of volleyball training, thus making it possible to prepare inputs that contribute to the comprehensive training of this investigated student population, by being able to merge psychomotor elements and the game of volleyball during scheduled classes.
Keywords: child psychomotricity; techniques; volleyball tactics; teaching strategies; psychomotor exercises